The electrostatic plasma environment of a small airless body under non-aligned plasma flow and UV conditions. (15th December 2015) - Poppe, A.R.; Zimmerman, M.I.; Halekas, J.S.; Farrell, W.M.
Abstract: Airless bodies interact with a wide variety of plasma environments throughout the solar system. For many objects, incident plasma is nearly co-aligned with solar ultraviolet radiation leading to the development of a positively charged dayside photoelectron sheath and a negatively charged nightside plasma sheath. Other objects, however, are present in environments where the plasma flow and solar UV radiation may not co-align. These environments include, for example, the moons of Mars as they pass through the deflected Martian magnetosheath, and many of the moons of the outer planets, which are embedded in co-rotating planetary magnetospheres. The decoupling of the plasma flow and UV incidence vectors opens up a wide range of possible surface charging and near-object plasma conditions as a function of the relative plasma-UV incidence angle. Here, we report on a series of simulations of the plasma interaction of a small body (effectively smaller than both electron and ion gyroradii) with both flowing plasma and UV radiation for different plasma-UV incidence angles using an electrostatic treecode model. We describe the plasma and electric field environment both on the object surface and in the interaction region surrounding the object, including complex surface charge and electric field distributions, interactions between surface-generated photoelectrons and ambient plasma electrons, and complex potential distributions, all of which vary as a function of the relative plasma flow-UV angle. We also show that in certain conditions, non-monotonic potential structures may exist around such objects, partially similar to those found at Earth's Moon. Abstract : Highlights: Use treecode to model electrostatics of body under non-aligned plasma flow/UV. Show the electrostatic potential, field, charge as a function of plasma/flow angle. Complex electrostatic environment: two-dimensional non-monotonic potentials. Potential applications for explaining observations at Moon and outer planet moons.